Addition of curcumin in dairy sheep diet in the control of subclinical mastitis - Jaguezeski A.M.* (2018)
© 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Curcumin, a polyphenol derived from rhizome of Curcuma longa, has been successfully used in animals and humans due to its antibacterial and anti-inflammatory properties. Recently, a study demonstrated that curcumin ointment reduced pain, mammary tension and erythema in humans with mastitis 72 h after the treatment. Mastitis in sheep is an important problem due to restrictions associated to the use of antibiotics, affecting milk production and becoming a public health issue. Thus, the aim of this study was to verify whether the addition of curcumin in the diet of six female sheep with subclinical mastitis could have curative efficacy and benefits to animal health. Cases: Six Lacaune sheep with subclinical mastitis that persisted for more than thirty days after the parturition were used. The animals received feed containing the curcumin (60 mg/animal/day) during 10 days. On days 0 and 10 of the experiment, total blood was collected to perform the hemogram and serum biochemistry (triglycerides, cholesterol, glucose, total protein (TP), albumin, globulin, aspartate aminotransferase (AST) and urea), as well as individual milk samples for centesimal composition, somatic cell count (SCC) and total bacterial count (TBC). Total leukocytes and erythrocytes, as well as hemoglobin content, were obtained using the hematological counter CELM-CC-550. Blood smears were stained by the Romanowsky method and used for leukocytes differentiation. After ten days of treatment, five sheep were negative in the California Mastitis Test (CMT). Total erythrocytes increased, while total leukocytes decreased after the treatment. Seric levels of AST, triglycerides, cholesterol and globulins decreased, while seric levels of albumin and urea increased after ten days of treatment. No differences were observed regarding milk production and composition, as well as for SCC and TBC on days 0 and 10 post-treatment. Discussion: The use curcumin to prevent or to delay the occurrence of subclinical mastitis in ewes was first tested. In an experiment of lipopolysaccharide-induced mastitis in rats, researchers identified receptors type Toll 4 which are related with the induction of the synthesis of pro-inflammatory cytokines, as tumor necrosis factor alpha, interleukin-6 and 1, molecules involved in the migration of leukocytes to the site of inflammation. According to literature, curcumin was able to reduce the activity of myeloperoxidase in the mammary gland, an enzyme used as indicator of neutrophil infiltration, demonstrating the potent anti-inflammatory effect of curcumin. This effect can be associated to the release of interleukin-8, a cytokine that promotes the migration of neutrophils, lymphocytes and eosinophils into the site of infection, i.e., the mammary gland. It is important to highlight that neutrophils, due to its capacity to release inflammatory mediators and to delay apoptosis, has the potential to maintain a permanent inflammatory process, effects that were prevented or reduced by curcumin, specially the apoptotic and cytotoxic effects. It is important to emphasize the direct effect of curcumin on bacteria present in the mammary gland, since it exerts potent bactericidal effect. In summary, the use of curcumin in sheep with subclinical mastitis exerted beneficial effects in the dose of 60 mg/sheep/day, since it showed 83.3% of curative efficacy in the test CMT. This effect of curcumin can be direct or indirect, since the curcumin provided in the diet showed anti-inflammatory properties by reducing oxidation reactions and cell damage. Overall, the addition of curcumin in sheep diet improved the hematological and biochemical variables after only ten days of treatment. Future studies should be performed to clarify and determine whether the curcumin provided in diet can be an alternative to treat clinical or subclinical mastitis.